Sources of trust in the healthcare context. A multilevel relationship with work engagement and organisational outcomes - Olvera, Juana; Acosta-Antognoni, Hedy; Llorens, Susana; Salanova, Marisa (Frontiers in Psychology, 2024)
Introduction The present study analysed the mediating role of interactional justice and horizontal trust between transformational leadership and organisational outcomes (i.e., job performance and service quality) at the work team level and the cross-level relationship of team horizontal trust with job performance at the individual level, controlling for work engagement based on the HERO Model. Methods Through structural equations and hierarchical linear models, the proposed hypotheses were addressed. The sample corresponds to 1,638 workers grouped into 109 work teams belonging to 28 hospitals in Spain. Results First, Structural Equation Modelling analysis revealed that, as expected, at the team level, interactional justice and horizontal trust mediate positive and significantly the relationship between transformational leadership and organisational outcomes (i.e., job performance and service quality). Secondly, the results of the Linear Hierarchical Models showed a positive relationship between work engagement and individual level performance. Finally, the multilevel analysis revealed that horizontal trust at the team level is positively related to work engagement at individual level; however, there is no cross-level relationship between horizontal trust at the team level and individual performance controlled by work engagement. Discussion Horizontal trust, at the team level, is positioned as a mediating variable between resources and organisational outcomes. Furthermore, it proves to be a key cross-level element for generating work engagement and job performance. The theoretical and practical implications of the study based on the HERO Model are discussed.